Predictors of Patients Who Present to the Emergency Department With Sepsis and Progress to Septic Shock Between 4 and 48 Hours of Emergency Department Arrival*. Issue 5 (May 2015) - Capp, Roberta; Horton, Cheryl Lynn; Takhar, Sukhjit S.; Ginde, Adit A.; Peak, David A.; Zane, Richard; Marill, Keith A.
<x xml:space="preserve">Abstract</x> Objectives: Approximately one in every four patients who present to the emergency department with sepsis progresses to septic shock within 72 hours of arrival. In this study, we describe key patient characteristics present within 4 hours of emergency department arrival that are associated with developing septic shock between 4 and 48 hours of emergency department arrival. Design and Setting: This study was a retrospective chart review study of all patients hospitalized from the emergency department with two or more systemic inflammatory response syndrome criteria present within 4 hours of emergency department arrival from September 2010 to February 2011 at two large academic institutions. Patients were excluded if they presented with a ST-elevation myocardial infarction, acute stroke, or trauma; had a cardiac arrest prior to arrival; were pregnant; or admitted from the emergency department psychiatric unit or transferred from an outside hospital. We identified patients with within 4 hours of emergency department arrival and identified those with septic shock at 48 hours after emergency department arrival, using a standard set of guidelines. The primary objective was identifying the number of patients who present with sepsis and progress to septic shock between 4 and 48 hours of emergency department arrival. As to the second objective, we used multivariate logistic regression analysis to identify patient factors associated with the progression of sepsis to septic shock for the aforementioned population. Measurements and Main Results: A total of 18, 100 patients were admitted from the emergency department, of which 3, 960 patients had two or more systemic inflammatory response syndrome criteria, and 1, 316 patients had sepsis within 4 hours of emergency department arrival. Although 50 patients presented to the emergency department with septic shock within 4 hours of arrival, 111 patients with sepsis (8.4%) progressed to septic shock between 4 and 48 hours of emergency department arrival. Characteristics associated with the progression of septic shock between 4 and 48 hours of emergency department arrival included female gender (odds ratio, 1.59; 95% CI, 1.02–2.47), nonpersistent hypotension (odds ratio, 6.24; 95% CI, 3.58–10.86), bandemia at least 10% (odds ratio, 2.60; 95% CI, 1.50–4.51), lactate at least 4.0 mmol/L (odds ratio, 5.30; 95% CI, 2.59–10.84), and past medical of coronary artery disease (odds ratio, 2.01; 95% 1.26–3.44). Conclusion: Approximately 12% of septic emergency department patients develop shock within 48 hours of presentation, and more than half of these patients develop shock after the first 4 hours of emergency department arrival. Over a third of patients who have sepsis within 4 hours of emergency department arrival and develop septic shock between 4 and 48 hours of emergency department arrival are not admitted to an ICU.